Farrerol inhibits proliferation and migration of colorectal cancer via the VEGF signaling pathway: evidence from network pharmacology, molecular docking, molecular dynamics simulation, and in vitro experiments - Zhang, Longhui; Xu, Qijing; Sun, Guanduo; Zhang, Xiaokang; Xue, Jialong; Yao, Chun; Liu, Dechun; Zhai, Jingming (Frontiers in Pharmacology, 2025)
ObjectiveAlthough farrerol exhibits promising antitumor properties against various cancers, its potential therapeutic effects on colorectal cancer (CRC) remain unexplored, and the underlying mechanisms are still unclear. Based on network pharmacology, molecular docking, molecular dynamics simulations, and in vitro experiments, this study aims to investigate the molecular mechanisms of farrerol in the treatment of CRC, thereby providing new research directions for CRC therapy.MethodsThis study employed network pharmacology to screen for potential therapeutic targets and pathways of farrerol in CRC, followed by preliminary validation of target validity through molecular docking and molecular dynamics simulations. Finally, in vitro experiments were conducted to verify the antitumor effects of farrerol against CRC.ResultsNetwork pharmacology identified 12 key targets: CCNA1, CCNA2, CCNE1, CDC25B, CDK2, CYP19A1, ESR1, ESR2, HSP90AA1, PTPN1, RAF1, and SRC. The molecular docking results revealed that the binding energies of farrerol with all target proteins were as follows: farrerol-CCNA1 (−8.6 kcal·mol-1), farrerol-CCNA2 (−7.0 kcal·mol-1), farrerol-CCNE1 (−7.4 kcal·mol1), farrerol-CDC25B (−7.3 kcal·mol-1), farrerol-CDK2 (−10.1 kcal·mol-1), farrerol-CYP19A1 (−8.4 kcal·mol-1), farrerol-ESR1 (−3.3 kcal·mol-1), farrerol-ESR2 (−8.9 kcal·mol-1), farrerol-HSP90AA1 (−10.4 kcal·mol-1), farrerol-PTPN1 (−7.6 kcal·mol-1), farrerol-RAF1 (−4.5 kcal·mol-1), farrerol-SRC (−9.9 kcal·mol-1), farrerol-VEGFA (−8.5 kcal·mol-1), and farrerol-KDR (−9.0 kcal·mol-1). These data indicate that farrerol can spontaneously bind to the target proteins. Molecular dynamics simulations demonstrated favorable interactions within the KDR-Farrerol and VEGFA-Farrerol complexes. In vitro experimental results demonstrated that farrerol could inhibit the proliferation and migration of CRC cells, induce cell cycle arrest at the G0/G1 phase, and suppress the protein expression of VEGFA, VEGFR2, and p-VEGFR2.ConclusionThis study, for the first time, validated the antitumor effect of farrerol against CRC through network pharmacology, molecular docking, molecular dynamics simulations, and in vitro experiments. The findings indicate that the ability of farrerol to inhibit the proliferation and migration of colorectal cancer cells may be associated with the induction of G0/G1 phase cell cycle arrest and the regulation of VEGF signaling pathway activation via binding to VEGFA and KDR.